PHYTOSANITARY ASSESSMENT OF THE STATE OF TROPICAL AND SUBTROPICAL PLANTS IN PROTECTED GROUND CONDITIONS (Experimental biology, 2022)
The research is based on the unique collections of tropical and subtropical plants of the MBG. Phytosanitary monitoring was carried out in the laboratory of «Tropical and Subtropical plants»: Orangery, glass greenhouse and Korean greenhouse. As a result of the phytosanitary monitoring of the greenhouse complex of the MBG, the next pests were identified: Trialeyrodes vaporariorum Westw.; Pseudococcus affinis Mask.; Diaspis boisduvalii Sign.; Tetranychus urticae L.; Myzodes persicae. Some plants were colonization by several pests at the same time. The spread of the sooty fungus is associated with the life activity of these pests. The pest infection of tropical and subtropical plants was evaluated and the most susceptible plants were identified. Plants of the family: Rutaceae, Moraceae, Malvaceae, Vitaceae and Palmae are susceptible to mass colonization of pests.
Keywords: pests, tropical and subtropical plants, orangery and greenhouse complex, plant protection